THE ROLES OF THE OFFICE OF RELIGIOUS AFFAIRS RELATING TO THE DISPENSATION FOR THE MARRIAGE OF UNDERAGE CHILDREN (CASE STUDY AMPAR DISTRICT, BATAM CITY) - Rudiansyah Rudiansyah; Ampuan Situmeang; Fl Yudhi Priyo Amboro (Universitas Internasional Batam, 2022)
Marriage of children who are still underage is often a problem because there are many conflicting factors occuring, namely age and health in child protection. Therefore, a rule is formed that regulates the age limit in marriage, but in practice there are still children who marry underage because they have received permission from the Religious Courts, namely the provision of marriage dispensation. In order to analyze this problem, this research uses the Theory of Authority by Miriam Budiardjo and the theory of Development Law by Mochtar Kusumaatmadja to analyze the obstacles faced by the Batam City Government in preventing the underage marriages in Batam City, especially in Batu Ampar District and to analyze solutions that can be taken to overcome the underage marriage in Batam City, especially in Batu Ampar District. The research found that the implementation of underage marriages in Batam City, especially in Batu Ampar District is carried out based on the limits of the authority of the Head of Religious Affairs Office and the existence of permission from the Religious Courts, namely the granting of marriage dispensation.